Inaugural Address (The Pakistan Development Review, 1994)
I deem it a privilege to inaugurate the Tenth Annual General Meeting of the Pakistan Society of Development Economists. It is with great satisfaction that I note the Society's contribution to increasing awareness about the process of economic development in general and about its unfolding in Pakistan in particular. Since its beginnings a decade ago, the Society has grown into an institution committed to the cause of development economics, which is to throw light on the ways and means of raising standards of living in developing countries. It has since broadened its scope as well as gained in depth. The Society and its office-bearers deserve our congratulations on these achievements. I am sure what we have seen of the Society's performance, especially on the occasion of the Annual General Meetings, is an earnest of more of the same in the future as well. We are today standing on the threshold of a profound transformation of the basic equations of the world economy. On the one hand, the old world order, based on the North-South divide, is being replaced gradually by a more complex system in which several rival economic blocks are emerging in the North as well as in the South. Unlike the past, the North is no longer the sole purveyor of capital and technical know-how, nor is the South completely dependent for its technical wherewithal on the North. On the other hand, with the disintegration of the Soviet Union, a unipolar political structure with obvious economic implications appears to be taking shape. Even though the overall picture of the New International Economic Order in the post-Cold War era still remains hazy, one thing is absolutely clear: the North as an engine of growth for the South has slowed down considerably and the relationship appears to be more one of interdependence, in which countries like Japan and South Korea have developed significant capital surpluses.